PENGARUH HARGA BELI TEBU, KUALITAS LAYANAN DAN REPUTASI PERUSAHAAN TERHADAP KEPUTUSAN PETANI MENJUAL TEBU DI PT. SINERGI GULA NUSANTARA (PABRIK GULA NGADIREDJO) - Bagas Aditya Putra; Heru Sutapa; Ahmad Jauhari (PT. Hasba Edukasi Mandiri, 2025)
The national sugar industry faces a significant challenge due to its heavy reliance on imports, making the continuity of sugarcane supply from farmers to sugar mills a critical factor. This study aims to analyze the effect of sugarcane purchase price, service quality, and corporate reputation on farmers’ decisions to sell sugarcane to PT. Sinergi Gula Nusantara (PG Ngadiredjo), Kediri Regency. The research employed a quantitative approach with a causal associative design. The sample was determined using purposive sampling, involving 33 farmers as respondents, and the data were analyzed through multiple linear regression. The findings indicate that the purchase price of sugarcane has a significant but negative effect on selling decisions, whereas service quality and corporate reputation exert a positive and significant influence. Simultaneously, the three variables significantly affect selling decisions, contributing 42.3%, while the remaining variance is explained by other factors beyond this study. These results highlight that farmer loyalty is not solely driven by price, but also by transparency in services and the company’s image. The implications of this research provide strategic recommendations for PG Ngadiredjo to review its pricing policies, improve service quality, and strengthen its reputation to sustain long-term partnerships with farmers.